Needs assessment to enhance public-private partnerships in smallholder irrigation development and management in Ethiopia - Seyoum, A.; Adamseged, Muluken Elias; Haileslassie, Amare; Ires, Idil; Jacobs-Mata, Inga (International Water Management Institute, 2025)
Ethiopia has significant untapped irrigation potential, but progress in the sector remains constrained by sole reliance on public investment, governance challenges, and limited private sector participation. Recognizing these issues, the Government of Ethiopia has prioritized Public-Private Partnerships (PPPs) as a strategy to accelerate irrigation development, enhance agricultural productivity, and improve rural livelihoods.